2014
DOI: 10.1590/s0103-90162014000100009
|View full text |Cite
|
Sign up to set email alerts
|

Breeding new sugarcane clones by mixed models under genotype by environmental interaction

Abstract: Sugarcane (Saccharum spp.) is one of the most important crops cultivated in the tropics and subtropics and plays a signifi cant economic and environmental role in Brazil. Twentyfour new clones were evaluated in different locations as potential models for recommendation as new varieties. The mixed model methodology, using the harmonic mean of the relative performance of genetic values (MHPRVG), facilitated the analysis of genotypic stability and adaptability, culminating in the recommendation of clones for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…The classification of accessions tolerant to PPD followed the same order for the two criteria ( i ĝ + µ and ), although estimates of the mean genotypic values were of low magnitude because the latter criterion considers the capitalization of the average interaction to reduce the mean value of the trait (less PPD severity). Similar observations were reported in sugarcane, in which the parameter permitted the capitalization of a larger proportion of sugar yield trait (Gonçalves et al, 2014). However, those authors warned that this superiority is only capitalized when the varieties are planted in areas with the same G x E interaction patterns.…”
Section: Genotypic Values Of the Ppd Tolerancesupporting
confidence: 64%
See 2 more Smart Citations
“…The classification of accessions tolerant to PPD followed the same order for the two criteria ( i ĝ + µ and ), although estimates of the mean genotypic values were of low magnitude because the latter criterion considers the capitalization of the average interaction to reduce the mean value of the trait (less PPD severity). Similar observations were reported in sugarcane, in which the parameter permitted the capitalization of a larger proportion of sugar yield trait (Gonçalves et al, 2014). However, those authors warned that this superiority is only capitalized when the varieties are planted in areas with the same G x E interaction patterns.…”
Section: Genotypic Values Of the Ppd Tolerancesupporting
confidence: 64%
“…Unlike that observed in the present study, Farias Neto et al (2013) reported complete agreement of the three most productive cassava genotypes based on Si, Ai, and Zi parameters. Gonçalves et al (2014) also demonstrated that all five sugarcane clones selected according to their Zi parameter also ranked as having the highest sugar yield. Therefore, those authors demonstrated an order of clone maintenance based on the Si, Ai, and Zi parameters, indicating that these methods have a certain degree of agreement between the positions of genotypes.…”
Section: Estimates Of Stability and Adaptability For Ppd Tolerancementioning
confidence: 85%
See 1 more Smart Citation
“…It also generates results in the unit itself, or in the scale of the evaluated trait, which can be interpreted directly as genetic values, which is not allowed by other methods. Moreover, this model also allows of additional inferences, such as: the selection of specific genotypes for each location; selection of stable genotypes in different locations; selection of genotypes (with high adaptability) which are responsive to the improvement of the environment; and the simultaneous selection for yield, stability, and adaptability (Gonçalves et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The simultaneous selection for yield, stability, and adaptability using mixed models can be accomplished by the harmonic mean of the relative performance of genetic values (HMRPGV) method (Carbonell et al, 2007;Gonçalves et al, 2014). This method, which was first proposed by Resende (2004), is similar to the methods of Annicchiarico (1992) and Lin and Binns (1988), and allows the simultaneous selection for yield, stability, and adaptability and considers phenotypic effects as random; therefore, it provides genotypic stability and adaptability.…”
Section: Introductionmentioning
confidence: 99%